PENGARUH KARAKTER DISIPLIN SISWA TERHADAP HASIL BELAJAR SISWA MADRASAH ALIYAH AL-MUSTAQIM ARANG LIMBUNG - Esti Susanti; Endang Purwaningsih; Rum Rosyid (Universitas Tanjungpura, 2019)
AbstractThe aim of this research was to know the influence of students discipline character through students achievement in economics study in the XII IPS of MA Al-Mustaqim Arang Limbung. The method of this research was quantitative descriptive. The sample of this research was all of students of twelve social programme which consists of 58 students. The writer collected the data by using indirect communication and documenter technique. The instrument of this research was questionnaire and students achievement document. The findings showed that the Sig as 0,004 smaller than alpha (the error) 0,05. So that Ha was accepted and H0 refused. It means that discipline character influence the students achievement and showed by linear equation system Y=41,470+0,331X and calculated hypothesis t-test>t table or 3,011>2,003. Therefove, the students discipline character through students achievement from this test was 0,139 or 13,9%. Keywords: Discipline character, Learning Outcomes